Perancangan Buku Company Profile PT. Texmura sebagai Media Promosi - Ananda Nofi Farahnisa; Muhammad Fauzi (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2026)
PT. Texmura is a sport court contractor company that has been established for over 20 years and operates throughout Indonesia. As a key player in the sport court construction industry, the company faces increasingly competitive rivalry, particularly from newer contractors leveraging digital media extensively. This situation necessitates a representative and professional printed promotional material that can comprehensively present the company's identity and portfolio. This design research aims to create a company profile book for PT. Texmura as an effective promotional medium to reach the institutional market segment. The method used is a qualitative approach through field study, official website observation, and SWOT analysis. The collected data was then processed into a design concept carrying a dynamic, modern, and sporty theme, in line with the company's business character. The design result is a portrait-format A4 company profile book containing a brief company profile, vision & mission, featured services, certifications, and documentation of completed projects. It is hoped that this company profile book can strengthen PT. Texmura's brand awareness among corporate clients, government bodies, and educational institutions.